The Influence of Truancy Behavior on Students’ Academic Achievement - Bait, Maria Della Strada; Dhiu, Margaretha (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Truancy behavior is a behavior where students do not attend lessons at school and of course this causes anxiety if it has a negative impact on students and also the school. The purpose of this study is to explain how the influence of truancy behavior on student learning performance. The method used is a literature study using 12 scientific articles that discuss truancy behavior and learning performance. The results of this study indicate that truancy behavior affects student learning performance, namely being given sanctions, suspension, being unable to take final exams, as well as a decrease in academic scores of the student, even being expelled from school. Truancy behavior can be overcome in various ways, one of which is counseling by experienced guidance and counseling teachers or by counselors. The factors causing truancy behavior are problems originating from oneself, family factors, and school factors with truancy behavior patterns such as playing playstation or the internet at internet cafes, hanging out, gathering with friends who like to skip school.